Socioeconomic and Racialethnic Disparities in Prosocial Health Attitudes: The Case of Human Papillomavirus (HPV) Vaccination for Adolescent Males - Polonijo, Andrea N. (J Health Soc Behav, 2016)
Research on prosocial attitudes, social networks, social capital, and social stratification suggest that lower- socioeconomic status (SES), Hispanic, and nonwhite individuals will be more likely than their higher-SES and non-Hispanic white counterparts to engage in health behaviors that serve a social good. Analyzing data from the University of North Carolina Human Papillomavirus (HPV) Immunization in Sons Study, we test whether SES and race-ethnicity are associated with willingness to vaccinate via prosocial attitudes toward HPV vaccination among adolescent males (n = 401) and parents (n = 518). Analyses revealed that (a) parents with lower education and (b) black and Hispanic parents and adolescent males reported higher prosocial vaccination attitudes, but only some attitudes were associated with higher willingness to vaccinate. We discuss these findings in terms of how prosocial attitudes may motivate certain health behaviors and serve as countervailing mechanisms in the (re)production of health disparities and promising targets of future public health interventions.